Photosynthesis and growth in diverse willow genotypes. (10th October 2014) - Andralojc, P. John; Bencze, Szilvia; Madgwick, Pippa J.; Philippe, Hélène; Powers, Stephen J.; Shield, Ian; Karp, Angela; Parry, Martin A. J.
Abstract During a study of the contribution of photosynthetic traits to biomass yield among 11 diverse species of willow, the light and CO2 dependence of photosynthesis were found to differ, with absolute rates at ambient and saturating CO2, together with maximum rates of Rubsico‐limited and electron‐transport‐limited photosynthesis (Vcmax and J, respectively) varying by factors in excess of 2 between the extremes of performance. In spite of this, the ratio, J/Vcmax – indicative of the relative investment of resource into RuBP regeneration and RuBP carboxylation – was found to fall within a narrow range (1.9–2.5) for all genotypes over two successive years. Photosynthetic rate (μmol CO2 fixed m−2 sec−1) showed a strong, inverse correlation with total leaf area per plant. Photosynthetic capacity, expressed on a leaf area basis, showed a strong, positive correlation with yield among some of the species, but when expressed on a whole plant basis all species indicated a positive correlation with yield. Thus, both leaf area per plant and photosynthetic rate per unit leaf area contribute to this relationship. The abundance and kinetic characteristics of Rubisco play a pivotal role in determining photosynthetic rate per unit leaf area and so were determined for the chosen willow species, in parallel with Rubisco large subunit (LSU) gene sequencing. Significant differences in the rate constants for carboxylation and oxygenation as well as the affinity for CO2 were identified, and rationalized in terms of LSU sequence polymorphism. Those LSU sequences with isoleucine instead of methionine at residue 309 had up to 29% higher carboxylase rate constants. Furthermore, the A/Ci curves predicted from each distinct set of Rubisco kinetic parameters under otherwise identical conditions indicated substantial differences in photosynthetic performance. Thus, genetic traits relating specifically to Rubisco and by implication to photosynthetic performance were also identified.